Transitioning towards sustainable agriculture: analysing the factors and impact of adopting multiple sustainable inputs by paddy farmers in India - Jha, Girish Kumar; Velayudhan, Praveen Koovalamkadu; Bhatia, Arti; Laishram, Chinglembi; Kumar, Deepak; Begho, Toritseju; Eory, Vera (Frontiers in Sustainable Food Systems, 2024)
Introduction: There is a global priority to ensure food security, environmental conservation and sustainability. The adoption of inputs such as organic manures, biofertilisers, and biopesticides has been widely promoted as a way to enhance agricultural sustainability, yet their adoption rates remain notably low. The study examines the determinants and impact of the adoption of multiple sustainable inputs by paddy farmers in India. The study also examines the drivers behind the intensity of their adoption and their technical efficiency. Method: The study utilises the survey dataset on paddy farmers from “Situation Assessment of Agricultural Households and Land and Livestock Holdings of Households in Rural India” of the 77th National Sample Survey (NSSO) round. The reference period for data collection was the agricultural year from July 2018 to June 2019. The analytical methods employed include the Multivariate Probit and Ordered Probit models, Seemingly Unrelated Regression, Regression Adjustment model, and Stochastic Frontier method. Results: The empirical findings reveal that the adoption and intensity of sustainable inputs depend significantly on factors such as the household head’s age and education, household size, and access to extension services. Adopting sustainable inputs has significant benefits, such as increased harvest value. However, the currently available technical advisory services are limited in effectively promoting the expenditure on sustainable inputs. Technical efficiency analysis underscores the potential for improvement and the importance of utilising optimal input levels. The research findings provide strong evidence in favour of advocating for the use of sustainable inputs in paddy farming.